Beauty's release : an erotic novel of discipline, love and surrender, for the enjoyment of men and women - Roquelaure, A. N. (Sleeping beauty trilogy, 1999)
"In this final volume of Anne Rice's deliciously tantalizing erotic trilogy, Beauty's adventures on the dark side of sexuality make her the bound captive of an Eastern Sultan and a prisoner in the exotic confines of the harem"--Page 4 of cover.